2020
DOI: 10.1590/1413-785220202802225137
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Functional Outcome of Oxford Phase 3 Unicompartmental Knee Arthroplasty

Abstract: Objective: To determine the factors that affect the functional outcome of Oxford Phase 3 unicompartmental knee arthroplasty (UKA). Methods: We assessed a total of 52 UKA knees of 49 patients with a minimum follow-up of 2 years (24-72 months). We recorded the results for Range of motion (ROM) and body mass index (BMI) and the presence o patello-femoral arthrosis (PFA). In the radiological evaluation, we measured the posterior tibial slope (PTS), the tibial plateau angle (TPA) and the femorotibial angle, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…In terms of survivorship, PTS, PCO and FSA were not associated with failures in this study. This finding was consistent with previous studies [7, 10], although some authors have reported PTS to be a crucial factor in UKA survivorship [26, 33]. The mechanism for this is because extremes of PTS has been shown to be a risk factor for bearing dislocation [36], although this is still contested [19, 24].…”
Section: Discussionsupporting
confidence: 91%
“…In terms of survivorship, PTS, PCO and FSA were not associated with failures in this study. This finding was consistent with previous studies [7, 10], although some authors have reported PTS to be a crucial factor in UKA survivorship [26, 33]. The mechanism for this is because extremes of PTS has been shown to be a risk factor for bearing dislocation [36], although this is still contested [19, 24].…”
Section: Discussionsupporting
confidence: 91%